HOW TO MAKE YOUR MEDIEVAL RESEARCH MORE VISIBLE WITH OPEN SCHOLARSHIP METHODS AND TOOLS. - WUTTKE, ULRIKE; GEBERT, BJORN (Imago Temporis. Medium Aevum, 2021)
Today research is in the midst of a global transformation that is usually referred to as Open Science. Open Science is a response from communities to global societal developments and to the digital transformation of research processes and leads to the emergence of new practices that are embedded in a digital ecosystem. The global Medieval Studies community is slowly adapting to this new culture that raises new questions around scientific practices. This article discusses three major pillars of Open Science: Open Access, Open Data, and Open Science Communication in the Digital Age. It considers the potential of these practices for individual researchers and for the role of medieval research in a modern society and explains good practices to start with.